Emergency Services Sector Protection and Homeland Security - Spellman, Frank R. (Bernan Press, 2023)
The fifteenth volume of a new, well-received and highly acclaimed series on critical infrastructure, Emergency Services Sector Protection and Homeland Security is an eye-opening account which discusses the unique challenges this industry faces and the deadly consequences that could result if there was a failure or disruption in the emergency services sector. The Emergency Services Sector (ESS) is crucial to all critical infrastructure sectors, as well as to the American public. As its operations provide the first line of defense for nearly all critical infrastructure sectors, a failure or disruption of the Emergency Services Sector (ESS) would be devastating. Emergency Services Sector Protection and Homeland Security was written to provide guidelines to improve the protections and resilience of this infrastructure.